Rebranding Logo dan Visualisasi Foto Produk UMKM di Kelurahan Gunung Anyar Tambak, Kota Surabaya - Prasetya, Shinta Rifianing; Hendrati, Ignatia Martha; Wardaya, Wirya (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This service to MSMEs in Gunung Anyar Tambak Village is focused on MSMEs that produce pastries. The purpose of this study was to find out the rebranding activities for making logos and images of MSME products in Gunung Anyar Tambak Village, Gunung Anyar District, precisely in the Gunung Anyar Emas Housing Complex (Rw 8) Surabaya City. The community service approach is used in this study. The results of the study show that logo rebranding is done by working on a logo that is already boring to be more assertive and attractive. Additionally, there are a number of stages involved in food photography design. The first step is to identify the data. The next stage is to develop inventive techniques considering the potential for food photography which puts forward new, solid and quality values using natural and natural visual designs that are friendly to clients. Keywords: logo design, photo visualization, rebranding, UMKM